Novel bivalent mucosal antigen formulation targeting SARS-CoV-2 and influenza: immunogenicity assessment using zan in vitro human nasal-associated lymphoid tissue model - Mahallawi, W.H. (Polish Journal of Veterinary Sciences, 2026)
The development of mucosal vaccines is crucial for controlling the transmission of respiratory viruses such as SARS-CoV-2 and influenza at their point of entry. This study aimed to validate a human tonsil-derived in vitro model for screening antigen formulation candidates and to evaluate the immunogenicity of a novel bivalent formulation. Mononuclear cells (MNCs) isolated from human palatine tonsils (n=20) were stimulated with full-length SARS-CoV-2 spike (S) glycoprotein, influenza A (H1N1) hemagglutinin (HA), or a combination of both (bivalent) at a concentration of 20 μg/mL. After a 10-day culture, antigen-specific IgG, IgM, and IgA antibody levels were quantified by enzyme-linked immunosorbent assay (ELISA). Stimulation with individual antigens elicited robust polyisotypic antibody responses. The S protein induced significant fold-increases over unstimulated controls for IgG (8.23, p<0.0001), IgM (5.77, p<0.0001) and IgA (4.56, p<0.0001). Similarly, the HA protein induced increases in IgG (7.16, p<0.0001), IgM (4.99, p<0.0001) and IgA (3.97, p<0.0001). Critically, bivalent stimulation resulted in superior additive responses. The anti-S component showed fold-increases of 11.09 (IgG, p<0.0001), 7.61 (IgM, p<0.0001) and 5.97 (IgA, p<0.0001). Similarly, the anti-HA component showed 9.66 (IgG, p<0.0001), 6.58 (IgM, p<0.0001) and 5.27 (IgA, p<0.0001), with no reduction in antigen-specific responses observed in the combined condition. The NALT model is a physiologically relevant platform for preclinical screening. It provides a compelling in vitro rationale for developing a bivalent intranasal antigen formulation to elicit potent mucosal immunity against major respiratory pathogens.